2016
DOI: 10.1590/s1678-994620160005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Permanent Staining Methods for the Laboratory Diagnosis of Trichomoniasis

Abstract: Trichomonas vaginalis is the etiologic agent of trichomoniasis, the most common non-viral sexually transmitted disease (STD) in the world. The diagnosis is based on wet mount preparation and direct microscopy on fixed and stained clinical specimens. The aim of this study was to compare the performance of different fixing and staining techniques used in the detection of T. vaginalis in urine. The smears were fixed and submitted to different methods of permanent staining and then, the morphological aspects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…[14] Giemsa stain is not appropriated since it stains only the nucleus of the organism. [12] Papanicolaou stained smear examination needs competence and expertise. False-positives as well as false negatives are common with this technique.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Giemsa stain is not appropriated since it stains only the nucleus of the organism. [12] Papanicolaou stained smear examination needs competence and expertise. False-positives as well as false negatives are common with this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Other staining and fixation methods have also been described in the literature, such as Giemsa and Gram staining. However, it has been demonstrated that Giemsa staining does not allow for the identification of the characteristic structures of the parasite, while Gram staining does not provide satisfactory fixation performance and the identification of morphological features [16]. Indeed, staining methods are not recommended in the clinical laboratory routine due to the potential for false negatives and false positives [7].…”
Section: Staining Techniquesmentioning
confidence: 99%
“…This review addresses laboratory diagnostic methods for T. vaginalis detection as well as an update on new methods that have been developed through patent filings around the world. The main methods currently available, described in Table 1, include: wet mount examination [14], cultural exam [15], staining [16], rapid tests [17,18], and molecular techniques based on nucleic acid amplification test (NAAT), such as conventional PCR [19,20], as well as other more recent tests for rapid identification that can often detect more than one sexually transmitted pathogen [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Smears-imprints were fixed with methanol for 3-5 minutes and stained according to the Romanovsky-Giemsa method. To identify trichomonads, smears were air-dried and stained with methylene blue, which made it possible to identify parasites by their morphological features (Menezes et al, 2016).…”
Section: Coproscopic Studiesmentioning
confidence: 99%